FROM SPACE TO EARTH: PHYSICAL AND BIOLOGICAL IMPACTS OF GLACIER DYNAMICS IN THE MARINE SYSTEM BY MEANS OF REMOTE SENSING AT ALMIRANTAZGO BAY, ANTARCTICA - Cardenas Mansilla, Carlos Alberto; Casassa, Gino; Aguilar, X.; Mojica, D.; Johnson Gavilan, Erling John; Brondi, F. (My University, 2020)
Abstract. To determine the biological and physical mechanisms between Lange glacier and its pro-glacier marine system located in Almirantazgo bay, King George Island, Antarctica, specific variables were determined through remote sensing approaches shown in this work. These preliminary results will allow relating the dynamics of both systems, the glacier, and the marine ecosystem. The information for the estimation of surface flux velocity of the glacier was derived through Radar satellite images (Sentinel-1) by means of offset tracking, the bathymetry was derived from a Multi-beam Echo Sounder, and the Digital Elevation Modell was obtained by means of a Remotely Piloted Aircraft; Finally, the biological parameters were derived from MODIS and OLCI images for the analysis of satellite data to have a first insight to the characteristics of the marine system. This information will help to build the first frame needed to study through remote sensing approaches, the mechanisms that govern the interface among “Lang Glacier” and the “Almirantazgo Bay” at King George Island, Antarctica.
Keywords: Glacier terminus